Domestic water quality monitoring at Seberang Perai Tengah, Pulau Pinang / Siti Rohany Sharuddin - Sharuddin, Siti Rohany (Faculty of Civil Engineering, 2006)
As Penang marches towards the 21st Century, our water demand will continue to increase, even as water supply issues become increasingly complex. As such, we need to manage water supply more effectively and innovatively. It also to determine the value of pH, suspended solid (SS), turbidity, residual chlorine and conductivity of the domestic water supplied in Seberang Perai Tengah according the sampling point are Kampung Paya, Kubang Semang, Kubang Ulu, Permatang Pasir and Permatang. The results obtained are expected to fulfill the Malaysian Standard and WHO. From the sampling result raw water and treated water, the results observed the change of the concentration of the sample before and after treatment for pH, turbidity and residual chlorine. The comparison were made between the result obtain with the standard quality of water. It is obtained that the result fulfills the Effluent Discharge Standards to Malaysian Inland Waters, Standard A. In water quality study, samples were taken from sampling points and treatment plants in Pulau Pinang. The laboratory test on water quality was conducted. The samples were taken one time every week, started from July 25, 2006 until August 29, 2006. Each sample taken was tested to determine the values of pH, SS, conductivity, turbidity and residual chlorine. The comparison were made between the result obtain with the standard quality of water. It is concluded that the result fulfills the National Standard for Drinking Water.